Community Participation and Government Role in Using Village Funds in Dlingo Village - Indah Nur Arifa (Policy & Governance Review, 2019)
This study discusses community participation and the role of the government in the utilization of village funds in Dlingo Village. The aim of this study was to find out about the level of community participation in the use of village funds in Dlingo Village and to find out about the role of the government in determining the use of village funds in Dlingo Village. This study uses Arnstein's theory of participation ladder, which is used to determine the level of community participation at each stage of development, namely planning, implementation, and monitoring and evaluation. The research method used is qualitative descriptive research method by collecting qualitative data in the form of interviews, document studies, and observations. The results of this study indicate that: (1) Community Participation in Development Program Planning is at the level of community participation at the partnership level. Community participation in the process is quite high, reaching 90% attendance at the village development planning meeting forum. (2) Community Participation in the Implementation of the Development Program is at the stage of placation, this is evidenced by the implementation of the program involving almost the entire community. The role of the village government as the manager of village funds in terms of implementing the program is as a coordinator so that each program can be implemented properly. (3) Community participation in the Development Program Monitoring and Evaluation is in the consultation stage where the community becomes a consultant to the village government. The role of the government is in the monitoring and evaluation process in terms of being a driver of supervision and evaluation among the community.